Phase Change Nanoelectromechanical Relay for Nonvolatile Low Leakage Switching. (9th April 2022) - Best, James T.; Masud, Mohammad Ayaz; de Boer, Maarten P.; Piazza, Gianluca
Abstract: The design, modeling, and experimental validation of a highly scalable phase change electromechanical relay are present. The Phase Change NEMS Relay (PCNR) is a nonvolatile mechanical relay actuated by the volumetric expansion of phase change material. GeTe is used as the active phase change material, and nonvolatile relay states are changed by converting it between amorphous and crystalline phases, which differ in volume by 10%. Phase conversion is induced by Joule heating an adjacent metal layer. Finite element analysis (FEA) models are developed to predict actuator temperature distributions and quench times for varied actuation pulses. Additional models are developed to simulate actuator deflection including reflow of molten phase change material during an actuation pulse. The smallest fabricated device has a heater footprint of 3 µm × 1 µm, with a 20 nm air‐gap. The FEA model, which calculates the actuation voltage, energy, and ON–OFF current ratio for this device to be 1.1 V, 42 nJ, and 10 8, respectively, are experimentally verified. A PCNR scaled down to a 15 nm × 5 nm heater footprint with a 2 nm air‐gap is predicted to actuate at 400 mV and 1.7 pJ. Abstract : The authors demonstrate a novel device design that incorporates the phase change properties of GeTe in a nanoscale electromechanical relay architecture. This highly scalable nonvolatile relay is an ideal candidate for energy‐constrained computing and memory applications as it offers high ON–OFF current ratio, very low leakage, and sub‐1 V actuation voltage.